Corneal Topography Pattern in Healthy Volunteers Coming to the Ophthalmology Department Hayatabad Medical Complex, Peshawar as Attendants - Mushtaq Ahmad, Naz Jehangir, Sofia Iqbal (Pakistan Journal of Ophthalmology, 2012)
Purpose: To determine the proportion of normal and abnormal topography patterns in attendants of patients coming to the Ophthalmology department Hayatabad Medical Complex, Peshawar. Material and Methods: It was a descriptive cross sectional study conducted at Ophthalmology department, Hayatabad Medical Complex, Peshawar from August 2009 to Feb 2010. Sample size was 91 individuals using Epi info 6 (Expected frequency of abnormal patterns is 39% with precision of 1- and confidence interval 95%) while simple random sampling technique was used. All health volunteers coming to the institute, both males and females with age ranged from 18 to 60 years were included in this study while Contact lens wearer, previous ocular surgery, previous ocular trauma, ocular surface disorders and refractive errors five diopter of hyperopia, myopia or astigmatism patients were excluded. SPSS version10 was used for analysis of the data. Results: We analyzed 182 eyes of 91 patients, 47 subjects were males and 44 were females. Abnormal patterns of corneal topography (asymmetric bow tie and irregular corneal topographic patterns) were seen in 77-79% of the people and normal patterns (oval, round and symmetric bow tie topographic patterns) were seen in 21-23% people. Conclusion: Due to the variability in corneal topographic patterns developing a meaningful classification system for our local people is a challenge. This study which is the 1st of its nature to be conducted in this area will help in providing a possible standard for corneal topography patterns for Khyber Pukhtoonkhwa local people.